Synthesis and evaluation of moxifloxacin derivatives for effects on proliferation and apoptosis of NCI-H1299 cells. Issue 21 (21st May 2020) - Yu, Fangmiao; Zhang, Zhuangwei; Li, Wei; Tian, Hengqun; Xu, Jun; Bao, Yongzhong
Graphical abstract: Highlights: New N-5-Aza ring derivatives of moxifloxacin. Cytotoxicity of 4-methyl derivatives on H1299 cells but not HUVEC cells. Induce characteristic apoptosis morphological changes in H1299 cells. Induce cell cycle arrest in G0/G1 phase. Induce both early and late apoptosis of H1299 cells. Abstract: Eight novel moxifloxacin (MXF) derivatives 4a-h were synthesized by functional modification of the N-5-Aza ring. Their growth inhibitory activities on human non-small lung cancer cell NCI-H1299 and A549 were evaluated by the MTT colorimetric assay. Based on the half inhibitory concentration (IC50 ) values, we determined that compounds 4b was the most efficacious derivative (IC50  = 2.56 ± 0.07 μM for NCI-H1299 and IC50  = 13.69 ± 0.70 μM for A549, respectively) that inhibited the proliferation of NCI-H1299 cells. Of these, Compound 4b (1 – cyclopropyl – 6 – fluoro – 8 – methoxy – 4 – oxo – 7 – ((4aS, 7aS) – 1 – (2 – oxo – 2 – (p – tolylamino) ethyl) hexahydro – 1H – pyrrolo [3, 4-b] pyridine – 6(2H)-yl) – 1, 4 – dihydroquinoline – 3-carboxylic acid) showed good potency against the growth of NCI-H1299 cells and also selectivity on HUVEC cells (IC50  > 500 μM). The dose-response relationship of the characteristic morphological changes of NCI-H1299 cells induced by Compound 4b was confirmed by AO/EB fluorescent staining. Furthermore, Compound 4b triggered apoptosis of NCI-H1299 in a concentration-dependent manner and arrested cells in the G0/G1 phase. These data indicate that the N-(p-tolyl)propanamide functionalized N-5-Aza ring of moxifloxacin may be a promising lead compound and candidate for the development of new agents against non-small-cell lung cancer.